Colposcopy of Female Genital Tract - Mehta, Sumita; Sachdeva, Poonam; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2017)
This book aims to promote awareness of and highlight the screening modalities and various treatment options available for the management of cervical pre-invasive lesions. Cervical cancer is the leading cause of malignancy among women worldwide, and deaths due to cervical cancer represent a global health problem. Yet the risk of cervical malignancy can be decreased substantially if the premalignant conditions of the cervix are recognized and treated in a timely manner. Colposcopy is the gold standard for the diagnosis of cervical dysplasia. Accordingly, the book details the fundamentals of colposcopy and colposcopic assessment of the normal and abnormal cervix. With preventive oncology taking front stage, colposcopy has become one of the most important diagnostic tools available. With chapters contributed by respected experts in this field, the book offers vital insights into colposcopy and an essential guide to comprehensive strategies for the early detection of cervical cancer. The main text is complemented by ample illustrations for clarity and a better understanding of the subject. Case discussions on various clinical scenarios will further ensure good clinical practices, which will in turn translate into reduced risk of cervical cancer.
Part I: Cervix -- Anatomy & physiology of cervix -- Pathology of pre-invasive lesions of cervix -- Part II: Screening for Cervical cancer -- Visual inspection methods for cervical cancer prevention -- Cytology as a screening tool -- Management recommendations in abnormal cytology -- HPV detection and clinical implications -- HPV Vaccination -- Part III: Colposcopy -- Colposcopy: The scientific basis -- Colposcopic technique, scoring and documentation -- Colposcopic appearance of normal cervix -- Colposcopic evaluation of pre-invasive & early cervical cancer -- Pre-invasive lesions in pregnancy& menopause -- Colposcopic examination in pregnancy -- CIN: Ablative Therapies -- Excisional procedures for treatment of intraepithelial lesions -- Colposcopy of vulva & vagina -- Part IV: Case discussions -- Cases. Appendix.
Keywords: Medicine; Obstetrics; Medicine & Public Health; Obstetrics/Perinatology.